Alkaline stripping for ultra clean bitumen from tar sand - Akande R.T.; Adeleke A.A.; Atanda P.O. (Journal of Mining and Metallurgy. Section A: Mining, 2019)
This study reports the recovery of bitumen concentrate from Ondo tar sand by alkaline leaching stripping of the associated sand. Bitumen was extracted from the tar sand as received in un-stirred and stirred state in the oven and on the magnetic stirrer hotplate, respectively, at varying 32 factorial design combinations of temperature and sodium hydroxide molar concentrations at 40 g/dm3 pulp density. The tar sand was further subjected to bitumen dissolution test and recovery of bitumen at varying pulp density. The results obtained showed that bitumen was optimally stripped from the tar sand with initial bitumen content of about 34% in the stirred condition to produce a concentrate with grade and recovery percents of 98.82 and 99.41% of bitumen, respectively. The optimal leaching stripping was obtained at 2 M sodium hydroxide concentration, at 90 °C temperature and 25 minutes contact time. The ultra-clean bitumen obtained can serve as raw material input for petroleum products recovery and as a coking additive in blend formulation of coals for metallurgical coke making.